Implementasi Algoritma J-Bit Encoding Pada Kompresi File PDF - Frida Effelyanti Naibaho (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Compression is a reduction in the size of the data to a smaller size than the original. The technique of compression is to replace the repetitive character with a certain pattern so that the data can minimize its size. Therefore the data that will be stored needs to be compressed first so that the size becomes smaller. The advantage of pdf files is that the pdf file format can not only store data in text form but also can save an image (image) or photo. In storing in pdf files, the data that will be stored is not susceptible to viruses. One pdf file compression technique that can compress images well is compressing pdf files using the J-Bit Encoding method. J-Bit Encoding (JBE) is an algorithm that optimizes input for other compression algorithms, thus the compression algorithm will be better if it is combined with the J-Bit Encoding method.